Gender perspective in UN framework for peace processes and transitional justice: the need for a clearer and more inclusive notion of gender - Lemay Langlois, Léa (International journal of transitional justice, 2018)
Gender influences the experiences of war and periods of large-scale abuses, and as such it needs to inform peace processes and transitional justice mechanisms. In the past 15 years, the UN Security Council has provided a framework for the inclusion of a gender perspective in peace processes, which includes attention to conflict-related gender-based violence (GBV) through the establishment of the Women Peace and Security (WPS) agenda. This article analyzes how gender is framed and understood in this context and how it impacts the practice of peace processes. It is suggested that in order to effectively tackle the root causes of conflict-related GBV, the WPS architecture should allow for an expansive understanding of gender, avoiding the reproduction of gender stereotypes. This should include the recognition of intersectional experiences of women with violence during conflict, violence based on sexual orientation and gender identity, and gendered violence committed against men.